1968
DOI: 10.1161/01.res.22.3.385
|View full text |Cite
|
Sign up to set email alerts
|

Role of Histamine in Hypoxic Pulmonary Hypertension in the Rat

Abstract: The present investigation was undertaken to see if any of the naturally occurring vasoactive substances was likely to act as a mediator for the pulmonary vasoconstrictor response to acute alveolar hypoxia. Rats were treated with agents that deplete local stores of vasoactive amines or inhibit their synthesis. Lungs from these animals were isolated, ventilated, and perfused with homologous blood at constant volume inflow. Their pressor responses to 2-to 3-minute periods of ventilation hypoxia (2% O 2 ) were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

1974
1974
1987
1987

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(19 citation statements)
references
References 12 publications
1
17
1
Order By: Relevance
“…Haas and Bergofsky (1972) have implicated mast cells in the hypoxic response of the lung by demonstrating that these are degranulated and that histamine release is increased in the hypoxic rat and guinea-pig. This work supported the earlier work of Hauge (1968), who used pharmacological agents to block or potentiate the effects of histamine during hypoxia to demonstrate a role for this agent, and suggested that histamine was involved in the hypoxic vasoconstrictor response. Adrenaline, however, antagonises the action of histamine (Colebatch, 1970), and it is possible that our differential reactivity is due to an increased delivery of adrenaline to the upper and lower lung zones that minimises the e£Fect of histamine.…”
Section: Discussionsupporting
confidence: 87%
“…Haas and Bergofsky (1972) have implicated mast cells in the hypoxic response of the lung by demonstrating that these are degranulated and that histamine release is increased in the hypoxic rat and guinea-pig. This work supported the earlier work of Hauge (1968), who used pharmacological agents to block or potentiate the effects of histamine during hypoxia to demonstrate a role for this agent, and suggested that histamine was involved in the hypoxic vasoconstrictor response. Adrenaline, however, antagonises the action of histamine (Colebatch, 1970), and it is possible that our differential reactivity is due to an increased delivery of adrenaline to the upper and lower lung zones that minimises the e£Fect of histamine.…”
Section: Discussionsupporting
confidence: 87%
“…A constrictor response can be demonstrated only with very large doses in this species [Hauge, 1968]. We attempted to inhibit the dilator action with metiamide but found that this drug diminished hypoxic vasoconstriction making it impossible to demonstrate further dilator effects.…”
Section: Ratsmentioning
confidence: 99%
“…Evidence in favour of histamine as a me diator of the pulmonary vascular response to hypoxia was provided by Hauge [1968]. Histamine was also implicated to play some role in the production of pulmonary oedema of high altitude because of its well-regulated property of alteration of blood vessel permeability [Luisada, 1950].…”
Section: Discussionmentioning
confidence: 99%
“…Antihistamines have been shown to prevent the development of hypoxic pulmonary hy pertension in experimental animals Susmanno and Carleton, 1973]. Histamine depletor substance 48/80 has also been shown to possess a similar effect [Hauge, 1968], Failure to observe a difference in the de gree of rise in the histamine level on admin istration of hypoxia between the 3 groups, makes it difficult to postulate that the de gree of rise in the histamine level, is the fac tor responsible for the susceptibility of cer tain subjects to develop POHA. However, it can be concluded with certainty that there is a very significant and consistent rise in the plasma histamine level within a short period of exposure to hypoxia and the available data thus suggest that histamine subserves an important function in mediating pulmon ary vascular response to hypoxia.…”
Section: Discussionmentioning
confidence: 99%